2020
DOI: 10.1097/md.0000000000020751
|View full text |Cite
|
Sign up to set email alerts
|

Mental health circumstances among health care workers and general public under the pandemic situation of COVID-19 (HOME-COVID-19)

Abstract: Background: After the spread of the coronavirus disease 2019 (COVID-19) globally, upgraded quarantine and physical distancing strategy, strict infection measures, and government's strict lockdown have been abided to confront the spread of the COVID-19 in Thailand. During the COVID-19 pandemic, concerns about the mental health and psychosocial problems among health care workers and the general population are now arising. Yet, information on mental health and psychosocial problems among health care w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
1
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 34 publications
4
70
1
16
Order By: Relevance
“…This was further validated by a pilot survey of 30 health care professionals and 30 individuals from the general population. Further details about the HOME-COVID-19 study have been provided in a previous study [ 21 ]. This was a nationwide survey conducted between April 21 and May 4, 2020.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This was further validated by a pilot survey of 30 health care professionals and 30 individuals from the general population. Further details about the HOME-COVID-19 study have been provided in a previous study [ 21 ]. This was a nationwide survey conducted between April 21 and May 4, 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Convenience sampling and a snowball strategy were used for participant recruitment through various social media networks (ie, public websites, Facebook, LINE, Twitter, and Instagram). The characteristics of the target population and the questionnaire used were subsequently presented [ 21 ]. We included Thai citizens, permanent residents, and nonresidents with employment or work permits who could read and communicate in the Thai language and were at least 18 years of age during the survey period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing surveys have been conducted all over the world to investigate psychological reactions and sleep changes in the general population [8][9][10], medical staff [11][12][13], as well as COVID-19 infected patients [14] and found that prevalence of stress, anxiety, depression and insomnia increased significantly during the COVID-19 pandemic [15][16][17][18][19][20]. Recently, two systematic reviews and meta-analyses further confirmed the negative impacts of COVID-19 outbreak on psychological reactions and insomnia [21,22].…”
Section: Introductionmentioning
confidence: 99%